Beyond Priesthood: religious entrepreneurs and innovators in the roman empire - Gordon, Richard L.; Petridou, Georgia; Rüpke, Jörg (Religionsgeschichtliche Versuche und Vorarbeiten, 2017)
This volume questions the established modern scholarly categories of priests and priesthood and focusses on processes of appropriation and contestation of religious expertise in the Imperial Era. It offers a unique insight into ancient religious specialists, their dynamic interaction with established religious authorities and institutions, and their contributions to religious innovation in the ancient Mediterranean world